Fluid-solid drag models selection for simulating wheat straw particle movement in anaerobic digester - Yang, Yang; Zhu, Hongguang (International Journal of Agricultural and Biological Engineering, 2023)
Computational fluid dynamics (CFD) has been utilized to simulate the movements of wheat straw particles for agitator speed selection in full-scale wet digestion. Previous research has found that the current drag model generally used for depicting the motion of spherical particles cannot match the movement behavior of wheat straw particles with their non-spherical shape. In this study, the sedimentation experiment and horizontal flow experiment of straw particles were determined using a V20-3D camera and a micro Particle Image Velocimetry (PIV) system. With analyses of the experimental data and CFD simulation results, the prediction accuracies of the non-spherical drag models of Hölzer and Sommerfeld (HS), Kishore and Gu (KG), Haider and Levenspiel (HL), Richter and Nikrityuk (RN), and Fabio Dioguardi (FD) were evaluated by the motion of individual straw particles. The results showed that the KG model has a significant advantage over the other drag models, both simulating the particle settling velocities in a one dimensional settling experiment and simulating the predictable trajectory in a two-dimensional horizontal flow experiment. Therefore, the KG drag model was selected to simulate with CFD the wheat straw particle movement to select agitator speeds. Additionally, the realizable k-ε turbulence model was proven to be superior to the other turbulence models for simulating the continuous phase flow with CFD.Key words: wheat straw particle, drag model, shape coefficient, image analysis, micro PIV measurementDOI: 10.25165/j.ijabe.20231602.8003Citation: Yang Y, Zhu H G. Fluid-solid drag models selection for simulating wheat straw particle movement in anaerobic digester. Int J Agric & Biol Eng, 2023; 16(2): 249–258.